The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.4082/kjfm.17.0041
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Adherence to Antihypertensive Medication

Abstract: BackgroundHypertension is a major contributor to the global disease burden of cardiovascular and cerebrovascular disease. The aim of this study was to determine demographic and clinical factors associated with adherence to antihypertensive medication.MethodsFrom August 2012 to February 2015, we recruited 1,523 Korean patients with hypertension who visited family physicians. The study was conducted in 24 facilities located in urban and metropolitan areas. Of these facilities, two were primary care clinics and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
51
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 23 publications
11
51
6
1
Order By: Relevance
“…The current study shows that, participants who were 64 and below years of age had higher level of treatment compliance compared to those with 65 and above years of age. These results are comparable to those reported from the study done in North America and Korea, reported older age showed association with treatment compliance [19,20]. The possible explanation of these results might be the truth that, the young people have higher income since they are able to work and thus can afford to buy medications than older people.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The current study shows that, participants who were 64 and below years of age had higher level of treatment compliance compared to those with 65 and above years of age. These results are comparable to those reported from the study done in North America and Korea, reported older age showed association with treatment compliance [19,20]. The possible explanation of these results might be the truth that, the young people have higher income since they are able to work and thus can afford to buy medications than older people.…”
Section: Discussionsupporting
confidence: 87%
“…Our findings showed compliance was higher than that of study conducted in Mumbai, reported 39.4% were compliant to their treatment [17]. The compliance was lower than that reported to the previous study in Korea and India [18,19]. The possible reason for the discrepancy observed could be explained by the types of hospitals included in our study, we included district hospitals, where participants attended are average Tanzanian compared to participants enrolled in the study conducted at Korea and India whom were from tertial hospitals with higher income and education, this could account for the difference observed.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…These significant predictors included the following: age (OR, 1.04; derstanding about the complications of A-HTNM, lack of social support, poor physician-patient relationship, and health care support affect adherence in different populations. 5,7,[23][24][25] Addressing these factors is very important for successful control and management of HTN. To the best of our knowledge, this is the first study to investigate adherence to A-HTNM and its associated factors among HTN patients attending primary health care centers in the Gaza Strip.…”
Section: Relationship Between Adherence Status and Predictorsmentioning
confidence: 99%
“…However, this finding is consistent with those of several other studies. 13,23,24) One reason for this finding could be that patients taking two or more pills recognize the severity of their disease and hence become more attentive to their treatment. In addition, taking multiple pills probably helped them avoid forgetting their medications.…”
Section: Relationship Between Adherence Status and Predictorsmentioning
confidence: 99%